THE PERFORMANCE AND EFFICIENCY RATING EVALUATION OF A HYDRAULIC RAM PUMP PROTOTYPE WITH HEIGHT VARIATIONS - M Fikri Radiyan; B S Wibowo; F T Sakti (Jurusan Teknik Sipil Universitas Bangka Belitung, 2019)
Initially, the prototype of a hydraulic ram pump was built using affordable tools and materials. Next, the experiment is divided into two stages. First, the experiment will evaluate the effect of different elevations of output pipe using three height variations (2, 3, 4 meters respectively) and two input discharge variations (7 and 8 liters/min respectively). The data collected from the experiment will yield six combinations of output discharge data which then be analyzed and discussed later in this paper. Second, the efficiency of this hydraulic ram pump will be calculated using a simple efficiency formula using the data output of the previous experiment. After that, the correlations between the height of the output pipe, input discharge, and efficiency will be concluded. Finally, the results showed that the highest efficiency (7.7%) was achieved using 8 L/min input discharge combined with 2 meters elevated output pipe. While the lowest efficiency (1.4%) was achieved using 7 L/min input discharge combined with 4 meters elevated output pipe.